Implementation Strategies And Implementation Problems On Jit Success In Smes - Tang, Wei Kee (2000)
Competitive intensity has increased continually, and at times dramatically, over the past 20 years. Firms, especially small-scale and medium-scale companies, that need to survive in this competitive business world must adopt new production system to upgrade their operation effectiveness. It is widely suggested that the adoption of just-in-time (JIT) leads to marked improvements in an organization's competitiveness and ability to respond to rapid fluctuations in market demand.